On the Cauchy Problem for 2b^ → -Parabolic Systems with Growing Coefficients - Ivasyshen, S. D.; Pasichnyk, H. S. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
For 2b^ → -parabolic dissipative systems and systems with growing coefficients as | x | → ∞ in the presence of degeneracies in the initial hyperplane, we investigate the fundamental matrix of solutions and the solvability of the Cauchy problem.